CDK12 antagonizes a viral suppressor of RNAi to modulate antiviral RNAi in Drosophila - Liqin Zhang; Yu Liang; Jiayu Qin; Chen Liu; Mengwei Shang; Xiaoming Sun (mBio)
ABSTRACT The primary antiviral immunity in insects is mediated by the RNA interference (RNAi) pathway. To counteract this antiviral RNAi response, viruses employ virulence factors known as viral suppressors of RNAi (VSR). The question of whether host factors can activate a counter-counter-defense mechanism to cope with VSR-mediated RNA silencing suppression remains unanswered. In this study, cyclin-dependent kinase 12 (CDK12) was identified to interact with B2, a VSR of Flock House virus (FHV), and the critical amino acids responsible for dsRNA binding and dimerization in B2 were essential for this interaction. Silencing of CDK12 facilitated FHV RNA accumulation only in the context of B2, not for FHVΔB2. Notably, CDK12 abrogated the RNAi suppression exerted by B2. Furthermore, the knockdown of CDK12 inhibited the production of vsiRNAs in FHV-infected Drosophila cells. This study revealed that CDK12 mediated a counter-counter-defense strategy against VSR, thereby enhancing antiviral RNAi immunity in Drosophila.IMPORTANCEThe arms race between virus and host immunity is never-ending. This study enhances our understanding of antiviral defenses in insects by uncovering a novel counter-counter-defense mechanism against viral suppressors of RNA interference (VSRs). The RNA interference (RNAi) pathway serves as a primary antiviral response in insects, but viruses, such as Flock House virus (FHV), have evolved VSRs like B2 to disrupt this defense. Our research identifies cyclin-dependent kinase 12 (CDK12) as a critical host factor that interacts with the VSR B2. The discovery that CDK12 can counteract B2-mediated RNAi suppression and stimulate the production of viral small interfering RNAs (vsiRNAs) in FHV-infected Drosophila cells highlights its pivotal role in enhancing antiviral RNAi immunity. This study not only reveals a new dimension of host-virus interactions but also opens avenues for developing strategies to strengthen RNAi-based antiviral defenses.